Ventricular arrhythmias. Ventricular tachycardias and sudden cardiac death. 2020 Clinical guidelines - D. S. Lebedev; E. N. Mikhailov; N. M. Neminuschiy; E. Z. Golukhova; V. E. Babokin; V. V. Bereznitskaya; E. S. Vasichkina; S. V. Garkina; S. P. Golitsyn; K. V. Davtyan; D. V. Duplyakov; E. V. Zaklyazminskaya; et al. (Российский кардиологический журнал, 2021)
Russian Society of Cardiology (RSC).With the participation of Russian Scientific Society of Clinical Electrophysiology, Arrhythmology and Cardiac Pacing, Russian Association of Pediatric Cardiologists, Society for Holter Monitoring and Noninvasive Electrocardiology.Approved by the Scientific and Practical Council of the Russian Ministry of Health.